Refleksje na temat monografii Ernsta Klee "Auschwitz. Medycyna III Rzeszy i jej ofiary" - Skorut, Jolanta (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
Auschwitz. Medicine of the Third Reich and Its Victims, Krakow 2009, second edition is one of the most shocking monographs ever written concerning Nazi crimes. Ernst Klee, German theologian and social pedagogue, recorded in it detailed descriptions of experiments conducted on human beings which were illustrated with horrifying photographs for example, of cut-off children’s heads placed in laboratory jars. He made use of a very rich source material and analyzed it so thoroughly that it is impossible to undermine his conclusions. Not only a monstrosity of the crimes committed in the name of medicine is shocking but also the fact that their perpetrators were scientists and doctors possessing established authority and undeniable achievements. Ernst Klee describes a number of pseudo-medical experiments, like applying hunger, using phenol, evoking typhoid fever, mass sterilization and experiments on twins. While analyzing the valuable monograph of E. Klee, I indicated Polish literature on the subject of pseudo-medical research and experiments. In reference to E. Klee’s monograph I formulated the following reflections: history of pseudo-medical experiments needs further scholarly, specialized investigations; it is worthwhile to accentuate significant achievements of Polish science that documented pseudo-medical experiments; it is necessary to attempt to fully explain the nature of compounds and specimens applied during pseudo-medical experiments; the interdisciplinary — medical and humanistic — character of research on the history of pseudomedical experiments is justified; interdisciplinary scientific research provides an opportunity for the further development of scholarly studies of Hitlerite crimes.
Keywords: Auschwitz; medycyna; III Rzesza; ofiara